2015
DOI: 10.5005/jp-journals-10006-1323
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Obstetric Hysterectomies at a Tertiary Referral Shri Vasantrao Naik Government Medical College and Hospital of Tribal of Yavatmal District (Maharashtra): Retrospective Critical Analysis (6 Years Study)

Abstract: Objective To evaluate the demographic profile, high-risk factors, fetomaternal outcome, causes and incidence of emergency peripartum hysterectomies at tertiary referral center Government Medical College and Hospital at Yavatmal. Study design Retrospective analysis. Methodology Review of 14 case records of patient who undergone emergency peripartum hysterectomies during the year January 2007 to December 2012. Results During the study period, there were 39,612 deliveries, out of which 14 patients had under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In Jayachawla et al, Vijarani et al and Rathod et al found atonic PPH common indication for periaprtum hysterectomy. 19,22,23 Out of 28 cases of emergency hysterectomy 3 cases were due to morbidly adherent placenta. Two were because of accrete and one case was done due to percreta.…”
Section: Maternal Outcomementioning
confidence: 99%
“…In Jayachawla et al, Vijarani et al and Rathod et al found atonic PPH common indication for periaprtum hysterectomy. 19,22,23 Out of 28 cases of emergency hysterectomy 3 cases were due to morbidly adherent placenta. Two were because of accrete and one case was done due to percreta.…”
Section: Maternal Outcomementioning
confidence: 99%